The age of Hirohito : - Irokawa, Daikichi (Free Press, 1995)
An insider's account of the development of a modern superpower offers a reassessment of Emperor Hirohito's incredible sixty-year reign, spanning the Depression, World War II, Hiroshima and Nagasaki, and the explosive recovery and growth of postwar Japan.